2014
DOI: 10.1071/mf13128
|View full text |Cite
|
Sign up to set email alerts
|

Ocean–estuarine connection for ichthyoplankton through the inlet channel of a temperate choked coastal lagoon (Argentina)

Abstract: We examined the fish larvae colonising pattern of the Mar Chiquita lagoon (Argentina). We hypothesised that in this microtidal lagoon, winds could regulate fish larvae dynamics. Ichthyoplankton samples were taken in marine waters, the surf zone and the estuary. Previous studies showed no reproduction by fishes with planktonic eggs inside the lagoon. However high abundance of eggs and larvae of Brevoortia aurea collected within the estuary also suggest possible spawning activity. Throughout the study period, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…Also, fish productivity inside estuarine systems (like the Patos Lagoon Estuary, Brazil) is highly dependent on the passage of weather fronts in spring when fish eggs are more abundant in the ocean (Martins et al 2007). Moreover, previous studies have demonstrated that onshore winds are key issues in the success of fish larvae recruitment from offshore spawning grounds to inner areas of Mar Chiquita instead of tides (Bruno et al 2014).…”
Section: Juvenile Fish Assemblages and Relationships With The Environmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, fish productivity inside estuarine systems (like the Patos Lagoon Estuary, Brazil) is highly dependent on the passage of weather fronts in spring when fish eggs are more abundant in the ocean (Martins et al 2007). Moreover, previous studies have demonstrated that onshore winds are key issues in the success of fish larvae recruitment from offshore spawning grounds to inner areas of Mar Chiquita instead of tides (Bruno et al 2014).…”
Section: Juvenile Fish Assemblages and Relationships With The Environmentioning
confidence: 99%
“…In contrast to larvae of other clupeoids from the northern hemisphere (B. tyrannus and B. patronus) (Powell 1994) that are spawned offshore and then drift towards the coast, B. aurea larvae in the Río de la Plata estuary are spawned and retained in estuarine waters (Acha and Macchi 2000). In Mar Chiquita coastal lagoon (~350 km southward of the Río de la Plata estuary) the occurrence of few individuals of B. aurea in advanced maturation ) and the high abundances of eggs and larvae of this species over the inlet channel (Bruno et al 2014) suggest that spawning activity may also occur inside this estuarine system. Nevertheless, the bulk of the spawning must be at sea given the dominance of post-flexion larvae on ichthyoplankton surveys conducted in the area (Bruno et al 2014).…”
Section: Spatial and Temporal Variation In Juvenile Fish Assemblagesmentioning
confidence: 99%
See 3 more Smart Citations